Research on the Failure and Fracture Evolution of Mylonite with a Prefabricated Circular Opening by Discrete Element Method - Kunmeng Li; Yuanhui Li; Shuai Xu; Zhipeng Xiong; Long An (Advances in Civil Engineering)
In this paper, the failure and fracture process of mylonite with a prefabricated circular opening under biaxial loading is studied by PFC2D code. Firstly, the hoop stress change law of opening wall in the process of loading is theoretically analyzed and three fracture patterns of rocks are proposed. Secondly, the biaxial loading tests of mylonite for numerical simulation are carried out, and the failure and fracture are analyzed from three aspects of space-time evolution of microcracks, energy conversion process, and final damage patterns. As the load progresses, the microcracks start to initiate at the side wall of the opening and the growth velocity of microcracks develops from the slow to fast and then slows down again. The final damage pattern of mylonite with a prefabricated circular opening belongs to shear fracture. The fracture zones start with the side wall spalling and then gradually extend to the border of the rock, which widen from the opening boundary to the border of the rock and slightly twist in the middle. The final fault zone width is about 6 times wider than the average size of simulation particles. Finally, based on the uniaxial compressive strength of mylonite in the laboratory, it is inferred that the fracture pattern of mylonite with a prefabricated circular opening by theoretical analysis is indeed shear failure, which is consistent with the result of numerical simulation.